Rituximab treatment in adults with refractory minimal change disease or focal segmental glomerulosclerosis - Ren, Hong (Oncotarget, 2017)
Rituximab (RTX) may benefit patients with glomerular disease who suffer from focal segmental glomerular sclerosis (FSGS) or minimal change disease (MCD). Here, we have described our experience treating 6 FSGS and 9 MCD patients with steroid-dependent/refractory nephrotic syndrome (NS) with RTX. Patients received RTX (375 mg/m2) intravenously on days 1, 8, 23, and 29. During a median follow-up of 8 months (range, 3-36 months) after RTX administration, all patients achieved complete or partial remission. Relapses decreased by approximately 30-fold compared with the year preceding RTX treatment, and an 89.27% reduction in proteinuria was observed. Furthermore, RTX treatment could decrease medical costs by 76.52% compared with the costs associated with the long-term use (for 12-13 months) of steroids and immunosuppressive drugs. In conclusion, RTX treatment was safe and effective for patients with refractory FSGS or MCD.